Formation and Development of Cadres of Peer Educators to Prevent and Mitigate the Impacts of Early Marriage in the Village of Pool, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra - Zuliah, Azmiati; Aflah; Hasibuan, Risma Laily; Simamora, Melky; Safnul, Dody (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service with the issue of early marriage is very important in order to encourage and empower the community, especially youth and village officials to be aware, know, have the capacity and participate in preventing and rejecting early marriage. Through this program socialization/campaign through KIE will be carried out in the Village of Pool, Percut Sei Tuan District, Deli Serdang Regency and training of peer educators and paralegals from the community in an effort to prevent early marriage. Through this program it is also hoped that there will be youth participation in the formation of a youth community and village apparatus formed through a Village Decree on Rejecting Early Marriage in the Village of Pond, Percut Sei Tuan District.